Prediction of heat flow through sand mould and its verification on the structure and property of gray cast iron - Shah, Sugrib Kumer; Haque, Md. Mohafizul; Maleque, Md. Abdul (Universiti Malaya, 2010)
Heat flows through the mould in casting govern the cooling rate of the liquid which affects the structure and properties of the materials. By controlling the heat flow direction, it is possible to control the structures as well as properties of the materials. To predict the heat-flow through the sand mould, finite element (FE) model was developed using FEA software. In order to verify the FE model, the gray cast iron was melted at 1350 0C temperature and poured into the sand mould at 1300 0C. The predicted and experimentally verified results show that maximum heat-reserve at the junction of the mould and the minimum at the end of the mould which increases with time at the thick section (10 mm). As a consequence, the solidification rate is higher at the end of the mould wall whereas it is comparatively lower near the sprue of the mould. It also shows that the microstructure and hardness change due to different heat flow through the sand mould.